2019
DOI: 10.3389/fvets.2019.00443
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Conditioned Medium From Amniotic Progenitor Cells in vitro and in vivo: Toward Tissue Regenerative Therapies for Bovine Mastitis

Abstract: There is increasing evidence to suggest that, in addition to their regenerative effect, mesenchymal stromal cells (MSCs), and their secretome have an anti-inflammatory and antimicrobial role in the innate immune response in conditions such as sepsis. However, there is no published information on the effect of MSCs in bovine mastitis. Mastitis often results in extensive tissue damage due to multi-microorganism co-infection. This study investigated the ability of amniotic-derived conditioned medium (CM), in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Encouraging reports have been recorded in the veterinary field, mainly in the treatment of mastitis models using CM from bovine bone marrow and adipose tissue MSCs [97]. In another study, CM treatment led to a lower rate of relapses than with antibiotic treatment [98].…”
Section: Mscs As Source Of Antibiotic-free Nanomaterialsmentioning
confidence: 99%
“…Encouraging reports have been recorded in the veterinary field, mainly in the treatment of mastitis models using CM from bovine bone marrow and adipose tissue MSCs [97]. In another study, CM treatment led to a lower rate of relapses than with antibiotic treatment [98].…”
Section: Mscs As Source Of Antibiotic-free Nanomaterialsmentioning
confidence: 99%
“…Ease of isolation was likely a factor in choosing BM or AT for some (Johnson et al, 2017;Cortés-Araya et al, 2018;Cahuascanco et al, 2019;Bujňáková et al, 2020;Peralta et al, 2020) and peripheral blood (PB) for others (Harman et al, 2017;Marx et al, 2020). Still, potency and lack of immunogenicity were also cited as reasons for choosing certain tissue sources, which led more than one group to isolate MSCs from fetal sources of BM, AT, or the amniotic membrane (Cahuascanco et al, 2019;Lange-Consiglio et al, 2019;Peralta et al, 2020). Although fetal and perinatal tissue-derived MSCs have been reported to be superior to their adult-derived counterparts in their proliferative potential and hypoimmunogenicity (Deus et al, 2020), it is as yet unclear what effect, if any, their more primitive state might have on their antimicrobial activity.…”
Section: Examples Of Antimicrobial Effect Of Msc In Domestic Animals mentioning
confidence: 99%
“…Consequently, the secretome can be influenced by culture conditions that activate or precondition MSCs to respond to the clinical problem at hand as discussed above. In the articles reviewed here, only two of the studies took strictly a cellular approach (Johnson et al, 2017;Peralta et al, 2020), one assessed both cells and CM (Harman et al, 2017), while the rest worked only with CM (Cortés-Araya et al, 2018;Cahuascanco et al, 2019;Lange-Consiglio et al, 2019;Bujňáková et al, 2020;Marx et al, 2020). Co-culturing equine PB-MSCs with either E. coli or S. aureus, Harman et al compared direct contact with transwell separation and found that both the cells and the paracrine factors alone had an inhibitory effect albeit somewhat muted in the case of the transwell setup (Harman et al, 2017).…”
Section: Examples Of Antimicrobial Effect Of Msc In Domestic Animals mentioning
confidence: 99%
See 2 more Smart Citations